Risk Factors And Prevalence Of Internet Addiction Among Adolescents: The Role Of Parental Supervision And Psychosocial Influences - Maria, Ima; Susanti, Febriyolla; Kashmir, Arifin Kurniawan; Kusdiyah, Erny (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: The rapid development of internet technology presents both opportunities and challenges, particularly internet addiction among adolescents, which impacts health, education, and social stability. In Indonesia, over 90% of adolescents are internet users, raising significant concerns. This study aims to determine the prevalence of internet addiction and identify contributing sociodemographic, behavioral, and psychosocial factors. Methods: A cross-sectional study was conducted involving 143 students from SMA Islam Al Azhar 8 Bekasi, selected through convenience sampling. Data were collected using a validated Internet Addiction Questionnaire and analyzed with bivariate and multivariate methods. Results: The prevalence of internet addiction was 34.27%. Significant factors included frequent violations of parental internet usage limits (OR=6.70; CI 95%: 1.76–25.56; p=0.005) and lack of participation in religious activities (OR=3.31; CI 95%: 1.09–10.04; p=0.034), indicating that weak parental control and low religious involvement increase the risk of internet addiction. Conclusion: Parental supervision, family support, and adolescent engagement in religious and social activities are crucial preventive measures. Interventions focusing on self-regulation, parental monitoring, and balanced internet use are recommended to reduce addiction risks.